1998
DOI: 10.1182/blood.v92.3.996.415k23_996_1002
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Agent Resveratrol, a Natural Product Derived From Grapes, Triggers CD95 Signaling-Dependent Apoptosis in Human Tumor Cells

Abstract: Resveratrol, a constituent of grapes and other food products, has been shown to prevent carcinogenesis in murine models. We report here that resveratrol induces apoptotic cell death in HL60 human leukemia cell line. Resveratrol-treated tumor cells exhibit a dose-dependent increase in externalization of inner membrane phosphatidylserine and in cellular content of subdiploid DNA, indicating loss of membrane phospholipid asymmetry and DNA fragmentation. Resveratrol-induced cell death is mediated by intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In a previous study made by Clement et al, it was demonstrated that resveratrol can induce programmed cell death in HL60 cells through death receptor . Similarly, Surh et al revealed the induction of apoptosis in HL60 cells by resveratrol .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In a previous study made by Clement et al, it was demonstrated that resveratrol can induce programmed cell death in HL60 cells through death receptor . Similarly, Surh et al revealed the induction of apoptosis in HL60 cells by resveratrol .…”
Section: Discussionmentioning
confidence: 93%
“…In a previous study made by Clement et al, it was demonstrated that resveratrol can induce programmed cell death in HL60 cells through death receptor. 26 Similarly, Surh et al revealed the induction of apoptosis in HL60 cells by resveratrol. 31 In this regard, Tsan et al also showed that the death receptors are not engaged in apoptosis induction and this programmed death may be a consequence of other different ways.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, several publications have revealed an elevated level of PDGF expression in clinical OS specimens. 18,25,26…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several publications have revealed an elevated level of PDGF expression in clinical OS specimens. 18,25,26 As seen in Figure 6, the expression of microRNA-4325p is associated with the angiogenesis induced by resveratrol in OS cells, which was thought to be involved in its regulation. Therefore, in this investigation, the effects were investigated of resveratrol on the putative target genes of microRNA-4325p by transiently transfecting MG-63 cells with the mimic or inhibitor, control miRNA or resveratrol (20 µM), followed by total RNA and real-time transcription-PCR analysis of the resulting RNA.…”
Section: Microrna-4325p Leads To Apoptosis Of Hos Cells By Negatively...mentioning
confidence: 96%